With the Quaid-i-Azam During His Last Days - Bakhsh, Ilahi, Lt. Colonel; Foreword by Jinnah, Fatima (Karachi, Pakistan Oxford University Press, 2011)
This is a first-hand account of the last days of the founder of Pakistan, the Quaid-i-Azam Mohammad Ali Jinnah written by Lieutenant Colonel Ilahi Bakhsh, a doctor of medicine, who was attending to Mohammad Ali Jinnah during his last illness. The narrative includes the author's conversations with M.A. Jinnah, together with an account of the author's diagnosis and treatment. This monograph is extremely valuable as it sheds light on the last two months of Mohammad Ali Jinnah's life while he struggled with his illness and finally lost. The author was one of the very few persons who were in personal contact with the Quaid-i-Azam at this time. This account is based on the author's entries in his personal diary. The book also sheds light on some traits of the Quaid, his demeanour, likes and dislikes, preferences and aversions, thus providing a glimpse into the personality of this great man.
Include Index.
Second edition published in 1978 by the Quaid-i-Azam Academy.
Keywords: Jinnah, Mahomed Ali, 1876-1948 -- Statesmen -- Pakistan -- Bakhsh, Ilahi, 1904-1960 -- Presidents -- Heads of state